Characterization of Rhesus Macaque Liver-Resident CD49a+ NK Cells During Retrovirus Infections - Ram, Daniel R.; Arias, Christian F.; Kroll, Kyle; Hueber, Brady; Manickam, Cordelia; Jones, Rhianna A.; Smith, Scott T.; Shah, Spandan V.; Varner, Valerie H.; Reeves, R. Keith (Frontiers in Immunology, 2020)
CD49a+ tissue resident NK cells have been implicated in memory-like NK cell responses, but while this population is well-characterized in mice and in humans, they are poorly described in non-human primates (NHP) which are particularly critical for modeling human viral infections. Others and we have shown that memory-like NK cells are enriched in the liver and because of the importance of NHP in modeling HIV infection, understanding the immunobiology of CD49a+ NK cells in SIV-infected rhesus macaques is critical to explore the role of this cell type in retroviral infections. In this study mononuclear cells isolated from livers, spleens, and peripheral whole blood were analyzed in acutely and chronically lentivirus-infected and experimentally-naïve Indian rhesus macaques (RM). NK cells were then identified as CD45+CD14−CD20−CD3−NKG2A/C+ cells and characterized using multiparametric flow-cytometry. Our data show that in RM, CD49a+ NK cells increase in the liver following retroviral infections [median = 5.2% (naïve) vs. median = 9.48% (SIV+) or median = 16.8% (SHIV+)]. In contrast, there is little change in CD49a+ NK frequencies in whole blood or spleens of matched animals. In agreement with human and murine data we also observed that CD49a+ NK cells were predominantly Eomeslow T-betlow, though these frequencies are elevated in infected animal cohorts. Functionally, our data suggests that infection alters TNF-α, IFN-γ, and CD107a expression in stimulated CD49a+ NK cells. Specifically, our analyses found a decrease in CD49a+ CD107a+ TNFα+ IFNγ− NK cells, with a simultaneous increase in CD49a+ CD107a+ TNFα− IFNγ+ NK cells and the non-responsive CD49a+ CD107a− TNFα− IFNγ− NK cell population following infection, suggesting both pathogenic and inflammatory changes in the NK cell functional profile. Our data also identified significant global differences in polyfunctionality between CD49a+ NK cells in the naïve and chronic (SHIV+) cohorts. Our work provides the first characterization of CD49a+ NK cells in tissues from RM. The significant similarities between CD49a+ NK cells from RM and what is reported from human samples justifies the importance of studying CD49a+ NK cells in this species to support preclinical animal model research.